Upaya Penurunan Kasus Infeksi Saluran Pernapasan Akut (ISPA) pada Prajurit di Polkes Brigif 22/OM - Prima Dewi K; ⁠Irma Aryanti (Jurnal Ragam Pengabdian, 2026)
Acute Respiratory Infection (ARI) remains one of the most common infectious diseases and continues to be a public health problem, including among military personnel. High mobility, intense social interaction, and suboptimal implementation of clean and healthy living behaviors increase the risk of ARI transmission among soldiers at Polkes Brigif 22/OM. This study aimed to identify the factors causing the high risk of ARI, determine priority problems, and develop intervention strategies through health education programs. The study used a descriptive approach with Fishbone analysis, USG (Urgency, Seriousness, Growth) analysis, and SWOT analysis. Data were collected through observation, interviews, and documentation studies. The results showed that the main problem was the inconsistent implementation of preventive behaviors such as wearing masks when sick, practicing proper cough etiquette, and maintaining personal hygiene. Based on USG analysis, suboptimal clean and healthy living behavior (PHBS) became the highest priority problem. SWOT analysis indicated that the organization was in Quadrant I (aggressive strategy), meaning that internal strengths and external opportunities could be optimized to support health education interventions. Health education activities involving 30 soldiers demonstrated an increase in the average score from approximately 60 during the pretest to 85 during the posttest. This finding indicates that health education effectively improved participants’ understanding and encouraged preventive behavior toward ARI. In addition, the SIAP ISPA digital education innovation was developed to support sustainable and accessible health promotion activities for soldiers.